Open-Label, Multicenter Study of Flecainide Acetate Oral Inhalation Solution for Acute Conversion of Recent-Onset, Symptomatic Atrial Fibrillation to Sinus Rhythm. (24th February 2022) - Crijns, Harry J.G.M.; Elvan, Arif; Al-Windy, Nadea; Tuininga, Ype S.; Badings, Erik; Aksoy, Ismail; Van Gelder, Isabelle C.; Madhavapeddi, Prashanti; Camm, A. John; Kowey, Peter R.; Ruskin, Jeremy N.; Belardinelli, Luiz; et al.
Abstract : Background: Oral and intravenous flecainide is recommended for cardioversion of atrial fibrillation. In this open-label, dose-escalation study, the feasibility of delivering flecainide via oral inhalation (flecainide acetate inhalation solution) for acute conversion was evaluated. We hypothesized that flecainide delivered by oral inhalation would quickly reach plasma concentrations sufficient to restore sinus rhythm in patients with recent-onset atrial fibrillation. Methods: Patients (n=101) with symptomatic atrial fibrillation (for ≤48 hours) self administered flecainide acetate inhalation solution using a nebulizer (30 mg [n=10], 60 mg [n=22], 90 mg [n=21], 120 mg [n=19], and 120 mg in a formulation containing saccharin [n=29]). Electrocardiograms and flecainide plasma concentrations were obtained, cardiac rhythm using 4-hour Holter was monitored, and adverse events were recorded. Results: Conversion rates increased with dose and with the maximum plasma concentrations of flecainide. At the highest dose, 48% of patients converted to sinus rhythm within 90 minutes from the start of inhalation. Among patients who achieved a maximum plasma concentration >200 ng/mL, the conversion rate within 90 minutes was 50%; for those who achieved a maximum plasma concentration <200 ng/mL, it was 24%. Conversion was rapid (median time to conversion of 8.1 minutes from the end of inhalation), and conversion led to symptom resolution in 86% of the responders. Adverse events were typically mild and transient and included: cough, throat pain, throat irritation; at the highest dose with the formulation containing saccharin, these adverse events were reported by 41%, 14%, and 3% of patients, respectively. Cardiac adverse events consistent with those observed with oral and intravenous flecainide were uncommon and included postconversion pauses (n=2), bradycardia (n=1), and atrial flutter with 1:1 atrioventricular conduction (n=1); none required treatment, and all resolved without sequelae. Conclusions: Administration of flecainide via oral inhalation was shown to be safe and to yield plasma concentrations of flecainide sufficient to restore sinus rhythm in patients with recent-onset atrial fibrillation. Registration: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT03539302.